Transforming traditional universities in The Kingdom of Saudi Arabia into smart universities in the light of employing artificial intelligence - Maghrabi, Rehab Saud (Journal of Educational and Psychological Sciences, 2023)
The study aimed to find out the importance of transforming traditional universities in the Kingdom of Saudi Arabia into smart universities in light of the employment of artificial intelligence and its obstacles from the point of view of the faculty members at Umm Al-Qura University. Umm Al-Qura University faculty members, and the study resulted in several results, the most important of which was: The study sample agreed to a large degree on the importance of transforming Saudi universities into smart universities using artificial intelligence tools and modern technologies, and they were very much about the obstacles to transforming traditional universities in the Kingdom of Saudi Arabia To smart universities in the light of employing artificial intelligence from the point of view of faculty members at Umm Al-Qura University. In light of this, the study recommended several recommendations, including: Establishing mechanisms to protect and secure the education digitization system (equipments/ networks/ programs/ applications/ platforms).